Reversible mutations in gliding motility and virulence genes: A flexible and efficient phage defence mechanism in Flavobacterium psychrophilum. (4th August 2022) - Jørgensen, Jóhanna; Sundell, Krister; Castillo, Daniel; Dramshøj, Liv S.; Jørgensen, Natasja B.; Madsen, Susie B.; Landor, Lotta; Wiklund, Tom; Donati, Valentina L.; Madsen, Lone; Dalsgaard, Inger; Middelboe, Mathias
Abstract: Flavobacteria are among the most important pathogens in freshwater salmonid aquaculture worldwide. Due to concerns regarding development of antibiotic resistance, phage therapy has been proposed as a solution to decrease pathogen load. However, application of phages is challenged by the development of phage resistance, and knowledge of the mechanisms and implications of phage resistance is therefore required. To study this, 27 phage‐resistant isolates of F. psychrophilum were genome sequenced and characterized to identify genetic modifications and evaluate changes in phenotypic traits, including virulence against rainbow trout. Phage‐resistant isolates showed reduction or loss of gliding motility, proteolytic activity, and adhesion to surfaces, and most isolates were completely non‐virulent against rainbow trout fry. Genomic analysis revealed that most phage‐resistant isolates had mutations in genes associated with gliding motility and virulence. Reversal of these mutations in a sub‐set of isolates led to regained motility, proteolytic activity, virulence and phage susceptibility. Although costly, the fast generation of phage resistance driven by single, reversible mutations likely represents a flexible and efficient phage defence mechanism in F. psychrophilum . The results further suggest that phage administration in aquaculture systems to prevent F. psychrophilum outbreaks selects for non‐virulent phage‐resistant phenotypes.